microRNA-1 Induces Transdifferentiation of Peripheral Blood CD34+ Cells into Cardiomyocytes-like Cells - Budi Susetio Pikir; Andrianto Andrianto; I Gde Rurus Suryawan; Hanestya Oky Hermawan; Dian Paramita Kartikasari; Primasitha Maharany Harsoyo (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Transdifferentiation is a method to provide cells sources for cellular cardiomyoplasty. CD34+ cells are potential cells sources because these cells can differentiate into cardiomyocytes through several mechanisms. MicroRNA (miR-1) is known to have the ability to inhibit the expression of histone deacetylase 4 (HDAC4). HDAC4 is a gene that essentially contributes in cardiomyocytes differentiation. However, the study reporting an evidence that miR-1 can induce transdifferentiation of CD34+ peripheral blood cells into mature cardiomyocytes is limited.METHODS: CD34+ cells were taken from peripheral blood and isolated using a magnetic-activated cell sorting (MACS) method in vitro. Mature mimics of miR-1 were transfected into isolated CD34+ cells and then incubated for 48 hours for quantification of HDAC4 mRNA using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). On the fifth day after miR-1 transfection, cardiomyocyte-like cells were identified based on their morphology and cardiac troponin expression using immunocytochemistry.RESULTS: Transfection of miR-1 in CD34+ isolated cells decreased HDAC4 gene expression by -0.54 fold at second day and caused a significant increase in percentage of cardiac troponin positive cells (median: 31.34; p<0.05) at fifth-day post-transfection. The efficiency of transdifferentiation was 32%. The miR-1 transfection had a significant negative relationship with HDAC4 gene expression (B=-1.000; p=0.001). HDAC4 gene expression had a negative and significant relationship with the percentage of cardiac troponin-positive cells (B=-0.701; p=0.001).CONCLUSION: This study suggests that miR-1 can induce transdifferentiation of peripheral blood CD34+ cells into cardiomyocytes-like cells by decreasing HDAC4 gene expression.KEYWORDS: transdifferentiation, microRNA-1, CD34, cardiomyocyte, HDAC4